Extensions to the core ontology for robotics and automation. (June 2015) - Fiorini, Sandro Rama; Carbonera, Joel Luis; Gonçalves, Paulo; Jorge, Vitor A.M.; Rey, Vítor Fortes; Haidegger, Tamás; Abel, Mara; Redfield, Signe A.; Balakirsky, Stephen; Ragavan, Veera; Li, Howard; Schlenoff, Craig; et al.
Abstract: The working group Ontologies for Robotics and Automation, sponsored by the IEEE Robotics & Automation Society, recently proposed a Core Ontology for Robotics and Automation (CORA). This ontology was developed to provide an unambiguous definition of core notions of robotics and related topics. It is based on SUMO, a top-level ontology of general concepts, and on ISO 8373:2012 standard, developed by the ISO/TC184/SC2 Working Group, which defines—in natural language—important terms in the domain of Robotics and Automation (R&A). In this paper, we introduce a set of ontologies that complement CORA with notions such as industrial design and positioning. We also introduce updates to CORA in order to provide more ontologically sound representations of autonomy and of robot parts. Abstract : Highlights: We discuss extensions to a core ontology for the robotics and automation field. The ontology aims to specify the main notions across robotics subdomains. We define robot, robotic system, robotic environment, and related notions. We discuss concepts regarding the notion of design, in industrial contexts. We discuss notions regarding the modes of operation of a robot. We discuss notions regarding the position, orientation and pose of a robot.